Comparative micromorphology of Costus pictus and Hellenia speciosa collected from Vietnam - Thanh Triet Nguyen; Van Chen Tran; Nguyen Xuan Lam Duong; Thi Thu Hien Nguyen; Thi Nga Nguyen; Thi Thuy Quynh Tran (Society for Indonesian Biodiversity, 2025)
Abstract. Triet NT, Chen TV, Lam DNX, Hien NTT, Nga NT, Quynh TTT. 2025. Comparative micromorphology of Costus pictus and Hellenia speciosa collected from Vietnam. Biodiversitas 26: 407-417. Costus pictus and Hellenia speciosa are two herbs belonging to the family Costaceae that have been used in traditional medicine to treat diabetes and are also used as daily food. The comparative anatomical characteristics between C. pictus and H. speciosa from Vietnam have not been systematically noted. This study aimed to develop microanatomical monographs of C. pictus and H. speciosa from Vietnam. Six fresh plants each were randomly collected for use in this study. Anatomical structures of rhizomes, roots, stems, and leaves were carried out using the iodine green-carmine staining method. The anatomical structural features of plant parts were analyzed and recorded through optical microscopy. The anatomical structural features of the tested samples are similar to those of Costus species. Notably, the anatomical structure of H. speciosa rhizome is similar to its stem, but different from that of C. pictus rhizome. The microstructures of their roots and leaves easily distinguish these species from each other. Additionally, smaller unicellular trichomes were observed in C. pictus leaves, while sub-air cavities, larger unicellular stout trichomes, and peltate glandular trichomes were found in H. speciosa leaves. The present evidence highlights the main structural features for distinguishing and identifying Vietnamese C. pictus and H. speciosa.